IKON KOTA SEMARANG - Murni Ediati (TEKNIK, 2009)
As we know that our forefather’s culture inheritance should protected such as the old historical building,monument and so on. We should not just close our eyes and then ignore it. Lawangsewu building is one ofthe old historical buildings as a landmark and icon for the City of Semarang. It is also a national culturalasset and one of the tourism resorts so basically it’s dealing with the Indonesian law, regulation and thegovernment’s authority.Actually there are a lot of foreign and domestic investors who want to use Lawangsewu building as a hotelbut usually it has been just a topic without an action. Nowadays, most of the historical buildings inSemarang are ‘lost’ and it has been uncountable how many of them were lost because of the economic andpolitical reason.The City of Semarang’s government has goodwill on planning and managing toward the Lawangsewubuilding because of the terribly condition of it (there is a lot of damaged because of a lot of exhibition weretook place in that building). One of the plans was about using it as Semarang Tourism and CultureDepartment, Semarang Centre of Tourism Information, Centre of Planning and Development Information ofThe City of Semarang.Recently there are some creative and innovative ideas appears to utilize the old historical buildings. Itmeans that now our people are understood about the significance of ‘the mute witness’ of our city’s history.Let us together make Semarang as the greatest city. For me the great city is the city which has a past,present and future. The great city always be an ideal city for all of us.